UNDERSTANDING EDUCATIONAL COSTS FOR POLICY AND DECISIONS IN PERIODS OF FINANCIAL CONSTRAINTS: A REVIEW OF CONCEPTS, THEORIES AND STRATEGIES - E. J. Isuku (African Journal of Educational Management, 2021)
This paper examined the importance of educational costs in the determination of the quantity and quality of education service available to the individual institution and the society at large. The paper reviewed the various cost concepts, theories and strategies that are germane in the course of providing educational services to a people or group particularly in periods of financial restrictions. It emphasized the necessity of understanding the implications of these various costs in the educational supply and demand analysis. The essence is to guide educational planners, policy makers and institutional managers to take appropriate decisions that will be most effective and efficient in the delivery of the needed educational services to all eligible citizens in the country.